IMPLEMENTASI BUSINESS MODEL CANVAS PADA UD MAKMUR MANDIRI - Maria Theresia Heni Widyarti; Hartono Hartono; Jati Handayani; Zulaika Putri Rokhimah; Septian Yudha Kusuma (Politeknik Negeri Semarang, 2023)
Business model Canvas (BMC) or Canvas Business Model can simply be interpreted as the process of how companies create value and benefit from the value it creates on an ongoing basis. BMC is a tool developed to help business organizations and budding entrepreneurs to map and analyze their business models. BMC transforms a complex business concept into a simple one that is displayed on a single sheet of canvas containing a business plan with nine well-integrated key elements including internal and external strategy analysis. This study aims to formulate and determine a business strategy in an effort to develop a business using the Business Model Canvas (BMC) model at UD Makmur Mandiri in Semarang.The method of analysis of this research is descriptive qualitative research. The data collection method used is library research and direct research by means of observation, interviews, and documentation. The research results are in the form of a Canvas Business Model table which contains nine key elements, namely Customer Segment, Customer Relations, Customer Channel, Revenue Structure, Value Proposition, Key Activities, Key Resources, Cost Structure, and Key Partners. In addition, a SWOT analysis was also presented based on the Canvas Business Model Table, which can provide input for UD Makmur Mandiri in formulating its business ideas, creating value and benefiting from the value it creates on an ongoing basis in managing its business